Potocki–shaffer deletion encompassing ALX4 in a patient with frontonasal dysplasia phenotype. Issue 2 (13th December 2013) - Ferrarini, Alessandra; Gaillard, Muriel; Guerry, Frederic; Ramelli, Gianpaolo; Heidi, Fodstad; Keddache, Caroline Verley; Wieland, Ilse; Beckmann, Jacques S.; Jaquemont, Sébastien; Martinet, Danielle
ABSTRACT Frontonasal dysplasia (FND) is a genetically heterogeneous malformation spectrum with marked hypertelorism, broad nasal tip and bifid nose. Only a small number of genes have been associated with FND phenotypes until now, the first gene being EFNB1, related to craniofrontonasal syndrome (CFNS) with craniosynostosis in addition, and more recently the aristaless‐like homeobox genes ALX3, ALX4, and ALX1, which have been related with distinct phenotypes named FND1, FND2, and FND3 respectively. We here report on a female patient presenting with severe FND features along with partial alopecia, hypogonadism and intellectual disability. While molecular investigations did not reveal mutations in any of the known genes, ALX4, ALX3, ALX1 and EFNB1, comparative genomic hybridization (array CGH) techniques showed a large heterozygous de novo deletion at 11p11.12p12, encompassing the ALX4 gene. Deletions in this region have been described in patients with Potocki–Shaffer syndrome (PSS), characterized by biparietal foramina, multiple exostoses, and intellectual disability. Although the patient reported herein manifests some overlapping features of FND and PPS, it is likely that the observed phenotype maybe due to a second unidentified mutation in the ALX4 gene. The phenotype will be discussed in view of the deleted region encompassing the ALX4 gene. © 2013 Wiley Periodicals, Inc.